Biocatalysis: Enzymatic Synthesis for Industrial Applications. Issue 1 (17th August 2020) - Wu, Shuke; Snajdrova, Radka; Moore, Jeffrey C.; Baldenius, Kai; Bornscheuer, Uwe T.
Abstract: Biocatalysis has found numerous applications in various fields as an alternative to chemical catalysis. The use of enzymes in organic synthesis, especially to make chiral compounds for pharmaceuticals as well for the flavors and fragrance industry, are the most prominent examples. In addition, biocatalysts are used on a large scale to make specialty and even bulk chemicals. This review intends to give illustrative examples in this field with a special focus on scalable chemical production using enzymes. It also discusses the opportunities and limitations of enzymatic syntheses using distinct examples and provides an outlook on emerging enzyme classes. Abstract : Biocatalysis has developed into a mature technology for chemical and pharmaceutical synthesis as well as other areas where high selectivity and mild reaction conditions are required. This Review highlights recent achievements with a special focus on industrialized applications including the introduction of key performance indicators (KPIs) to judge the efficiency of enzymes.